Management of mattresses in the prevention of healthcare-associated infection: a cross-sectional study - Giroti, Alessandra Lyrio Barbosa; Ferreira, Adriano Menis; Cury, Elenir Rose Jardim; Rigotti, Marcelo Alessandro; Carneiro, Liliane Moretti; Diniz, Maiara Oliveira (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Healthcare Associated Infection (HAI) threatens patient safety and can be associated with contamination of surfaces such as mattresses. This study aimed to identify the criteria for the acquisition and conservation of mattresses in hospitals and Homes for the Aged (HA) as an infection prevention strategy. Outlining: Cross-sectional study carried out with 18 institutions. Data were collected through a structured interview with the person responsible for administration, hospitality sector or the Hospital Infection Control Committee, using a validated instrument. Data analysis was performed using descriptive statistics. Results: Five HA and 8 Hospitals partook the study. Acquisition by direct purchase prevails (94.4%), with a periodicity of 1 to 5 years (50%). All mattresses purchased are foam ones, due to user comfort (44.4%) and resistance (38.9%). Waterproof cover is used by 83% of the services, made of “napa” (72.2%) and “corvin” (66.7%) for easy sanitizing (77.8%). “During the concurrent cleaning” is the most mentioned time to evaluate the integrity of the mattress (38.8%) and coating (50%). Implications: it was observed that there is no systematic management for the acquisition and maintenance of mattresses. This highlights the need to improve the care with patient bed in order to prevent healthcare-associated infections.